Laser irradiation inhibition of open gingival embrasure space after orthodontic treatment - Meguro Daijiro; Yamaguchi Masaru; Kasai Kazutaka (Sciendo, 2002)
The purpose of this study was to investigate the inhibitory effect of low-energy laser irradiation on an incidence of open gingival embrasure space after orthodontic treatment. The patient was a 20-year, 7-month-old Japanese female with an Angle Class I malocclusion and crowding in the mandible. Treatment consisted of extraction of maxillary and mandibular first premolars and use of the Edgewise technique.